Establishment and characterization of macrophage cell line from thymus of Catla catla (Hamilton, 1822). Issue 2 (12th July 2012) - Chaudhary, Dharmendra Kumar; Sood, Neeraj; Rathore, Gaurav; Pradhan, Pravata Kumar; Punia, Peyush; Agarwal, Naresh Kumar; Jena, Joy Krushna
Abstract A continuous cell line has been developed from thymus explants of Catla catla and the cells have been subcultured for 63 passages. The cells exhibited optimum growth at 30°C in L‐15 medium containing 15% foetal bovine serum. The cultured cells engulfed yeast cells and fluorescent latex beads. These cells produced reactive oxygen and nitrogen intermediates following stimulation with lipopolysaccharide and phorbol esters. The culture supernatant from the cultured cells had lysozyme activity and these cells demonstrated Fc receptors. Almost all the cells were positive for alpha‐naphthyl acetate esterase enzyme suggesting that the cells are of macrophage lineage and therefore, the cell line was designated as catla thymus macrophage (CTM) cell line. CTM cells formed aggregates around zoospores of Aphanomyces invadans, but were unable to inhibit the germination of spores. The karyotype analysis of CTM cells at 25th passage revealed a typical diploid model with 50 chromosomes per cell. Partial amplification, sequencing and alignment of fragments of two mitochondrial genes 16S rRNA and cytochrome c oxidase subunit 1 confirmed that the CTM cell line originated from C. catla. This cell line should be useful for studying the role of macrophages in differentiation and maturation of thymocytes and can be a source of macrophage‐specific enzymes and cytokines.